A Single Atom Antenna. (August 2015) - Trinter, Florian; Williams, Joshua B; Weller, Miriam; Waitz, Markus; Pitzer, Martin; Voigtsberger, Jörg; Schober, Carl; Kastirke, Gregor; Müller, Christian; Goihl, Christoph; Burzynski, Phillip; Wiegandt, Florian; et al.
Synopsis: Here we demonstrate the smallest possible implementation of an antenna-receiver complex which consists of a single (helium) atom acting as the antenna and a second (neon) atom acting as a receiver.